Design of pyramidal microwave absorber using agriculture waste with different resin content percentage - Nornikman, Hassan; Soh, Ping Jack; Azremi, Abdullah Al Hadi; Wee, Fwen Hoon (Universiti Malaysia Pahang (UMP), 2010)
MUCEET 2009 is organized by Malaysian Technical Universities Network (MTUN) comprising of Universiti Malaysia Perlis (UniMAP), Universiti Tun Hussein Onn (UTHM), Universiti Teknikal Melaka (UTeM) and Universiti Malaysia Pahang (UMP), 20th - 22nd June 2009 at M. S. Garden Hotel, Kuantan, Pahang.